Parity Demystified - CARLSON, ERIK (Theoria (Lund, Sweden), 2010)
Ruth Chang has defended a concept of “parity”, implying that two items may be evaluatively comparable even though neither item is better than or equally good as the other. This article takes no stand on whether there actually are cases of parity. Its aim is only to make the hitherto somewhat obscure notion of parity more precise, by defining it in terms of the standard value relations. Given certain plausible assumptions, the suggested definiens is shown to state a necessary and sufficient condition for parity, as this relation is envisaged by Chang.